Poverty As Inefficiency of the Welfare State. A Cross Country Comparison - Mats Lindblom; Bjorn Gustafsson (Luxembourg Income Study (LIS), 1990)
This paper uses LIS data to calculate poverty lines for ten countries - setting the poverty line equal to the average disposable income for families in the working age but have no income from working or capital.
Keywords: 330